2009
DOI: 10.1021/nl901138p
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Mobility in Nanoporous Glass Films

Abstract: Polymer molecules when physically confined at nanometer length scales diffuse nonclassically and very differently depending on their molecular weight and the nature of the confinement. Long polymers that exhibit "snakelike" reptation based mobility in melts may diffuse faster in confined nanometer sized cylinders with pore diameter d approximately 15 nm, and short polymers subject to Rouse dynamics have shown signatures of reptation and slower diffusion when confined in nanoporous glass with d approximately 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…We recently showed that unentangled surfactant molecules in the bulk become entangled with adjacent molecules when diffusing through interconnected nanopores (d ∼ 2.1 nm) and exhibit signatures of reptation. 9 We also discussed the importance of molecular interactions with pore surfaces. Other studies have shown that long polystyrene molecules with molecular weight above that needed for entanglement diffuse faster in cylindrical alumina nanopores (pore diameter d ∼ 15 nm) due to lower molecular entanglement associated with fewer chains present in the confined region.…”
Section: Abstract Molecular Mobility Nanoporous Nanoconfinementmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently showed that unentangled surfactant molecules in the bulk become entangled with adjacent molecules when diffusing through interconnected nanopores (d ∼ 2.1 nm) and exhibit signatures of reptation. 9 We also discussed the importance of molecular interactions with pore surfaces. Other studies have shown that long polystyrene molecules with molecular weight above that needed for entanglement diffuse faster in cylindrical alumina nanopores (pore diameter d ∼ 15 nm) due to lower molecular entanglement associated with fewer chains present in the confined region.…”
Section: Abstract Molecular Mobility Nanoporous Nanoconfinementmentioning
confidence: 99%
“…The final film thickness, h ∼ 500 nm, density, F ∼ 1.06 g/cm 3 , pore diameter, d ∼ 2.1 nm, and dielectric constant, k ∼ 2.3, were measured. 9 The MSSQ glass matrix is a structurally modified form of silica produced by replacing one bridging oxygen atom with a terminal methyl group yielding a film with reduced k and strong hydrophobicity (contact angle with water >100°). Organosilicate glass (OSG) and porogen-containing organosilicate glass (pOSG) films with similar composition but more disordered molecular structure were deposited on Si substrates by plasma-enhanced chemical vapor deposition (PECVD) and cured with broad-band UV radiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the HLB of the surfactants plays a very crucial role in the spreading behavior. In our experiments, the HLB of the surfactants was calculated by Griffin's method [42,43]: HLB = 20*M h /M, where M h is the molecular mass of the hydrophilic portion of the molecule and M is the molecular mass of the whole molecule. The HLB values of S m (EO) n are listed in Table 1.…”
Section: Dynamic Spreading Behavior Of the Surfactants On Plant Leaf mentioning
confidence: 99%